PENGARUH HEDONIC SHOPPING MOTIVES TERHADAP SHOPPING LIFESTYLE - Ningrum, Wintari Devita (Fakultas Ekonomi Universitas Wisnuwardhana, 2023)
Abstract: This study aims to (1) know and explain how the characteristics of male fashion product respondents in Malang, (2) know and explain the factors that make up the Hedonic Shopping Motives, (3) know and explain how much influence the determinant of Hedonic Shopping Motives on Shopping Lifestyle. This type of research is an explanatory quantitative approach. The variables of this study include Hedonic Shopping Motives, and Shopping Lifestyle. The population in this study is the male community of fashion product users in the city of Malang. The sample used in this study were 152 respondents taken using incidental sampling techniques and data collection methods using a questionnaire or questionnaire. Data analysis used was descriptive statistical analysis, classical assumption test, inferential statistical analysis (Exploratory Factor Analysis and Regression Analysis). The data in this study were processed using SPSS 23 for Mac. The analysis shows that there are four factors that make up the Hedonic Shopping Motives, namely the Value Shopping Factor (F1), the Idean Shopping Factor (F2), the Social Shopping Factor (F3), the Adventure Shopping Factor (F4) which has a significant effect on the Shopping Lifestyle (Y) . The results of the analysis show that the Value Shopping Factor (F1) is the dominant factor in influencing Shopping Lifestyle (Y). Based on the research results, it is better for business people or marketers to create a comfortable shopping atmosphere in terms of products, services and shopping convenience. A comfortable shopping atmosphere in terms of products that is business people or suppliers can provide the best offers in the form of discounts or discounts so that it can meet the Value Shopping of male fashion product users in Malang.Keywords: Hedonic Shopping Motives, Shopping Lifestyle.Abstrak: Studi ini bertujuan untuk (1) mengetahui dan menjelaskan bagaimana karakteristik produk fashion pria responden di Malang, (2) tahu dan menjelaskan faktor-faktor yang membentuk Motif Belanja Hedonik, (3) tahu dan menerangkan seberapa banyak pengaruh determinan Motif Beli Hedonis pada Gaya Hidup Belanja. Jenis penelitian ini adalah pendekatan kuantitatif yang menjelaskan. Variabel-variabel penelitian ini meliputi Hedonic Shopping Motives, dan Shopping Lifestyle. Populasi dalam penelitian ini adalah komunitas pria pengguna produk fashion di kota Malang. Sampel yang digunakan dalam penelitian ini adalah 152 responden yang diambil menggunakan teknik sampling acak dan metode pengumpulan data menggunakan kuesioner atau kuesional. Analisis data yang digunakan adalah analisis deskriptif statistik, tes asumsi klasik, analisis statistik inferensial (Exploratory Factor Analysis and Regression Analysis). Data dalam penelitian ini diproses menggunakan SPSS 23 untuk Mac. Analisis menunjukkan bahwa ada empat faktor yang membentuk Motif Belanja Hedonik, yaitu Value Shopping Factor (F1), Idean Shopping Faktor (F2), Social Shopping Facter (F3),Arthavidya Jurnal Ilmiah Ekonomi Desember 2023 | 453dan Adventure Shopping Factory (F4) yang memiliki efek signifikan pada gaya hidup Belanja (Y). Hasil analisis menunjukkan bahwa Value Shopping Factor (F1) adalah faktor dominan dalam mempengaruhi gaya hidup belanja. (Y). Berdasarkan hasil penelitian, lebih baik bagi orang-orang bisnis atau pemasar untuk menciptakan suasana belanja yang nyaman dalam hal produk, layanan, dan kenyamanan belanja. Suasana belanja yang nyaman dalam hal produk yang merupakan orang bisnis atau pemasok dapat memberikan penawaran terbaik dalam bentuk diskon atau diskon sehingga dapat memenuhi Value Shopping pengguna produk fashion laki-laki di Malang.Kata kunci: Hedonic Shopping Motives, Shopping Lifestyle.